Influence of slip velocity on convective boundary layer flow of Jeffrey fluid under convective boundary conditions - Al-Sharif, H. A. M.; Kasim, A. R. M.; Salleh, M. Z.; Md. Sarif, N.; Mohammad, Nurul Farahain; Shafie, S.; Ali, A. (Asian Research Publishing Network, 2016)
The problem on influence of slip velocity on convective boundary layer flow of Jeffery fluid with convective boundary conditions together with the effects of magnetohydrodynamic is investigated. The governing equations correspond to the discussed problem are first transformed into ordinary differential equations using similarity transformations before the computation process is done by Keller box method. It is found that, the magnetic parameter enhanced the fluid temperature and lowers the velocity of the fluid flow while the growth of the values of Prandtl and Deborah number weaken the distribution of the fluid temperature.